STUDI METODOLOGIS KITAB MISBAH AL-ZULAM KARYA K.H. MUHAJIRIN AMSAR - Moh. Ashif Fuadi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2023)
This study discusses the character of K.H. Muhajirin Amsar and a methodological study of his work, namely the book Misbah al-Zulam. This research uses the library research method (literature study) by studying the book Misbah al-Zulam, reinforced by secondary data sourced from books, articles, and online news relevant to the theme raised. This research concluded that, first, K.H. Muhajirin Amsar is an influential contemporary scholar from Bekasi who is quite productive in producing works in the form of typical pesantren books, including 34 books from 8 Islamic religious disciplines reflecting the depth and breadth of his knowledge. Of his works, the most popular is the book Misbah al-Zulam which consists of 8 volumes which is a sharh or follow-up explanation of the book Bulugh al-Maram by Ibn Hajar al-Asqalani. Second, there are three methods of writing the book of Misbah al-Zulam: tanqil (quoting), tabyid (sorting), and tahqiq (strengthening). The tanqil method means quoting from the literature used as a reference, while the tabyid method means sorting out manuscripts more relevant to the theme. The tahqiq method is to strengthen the work written as a whole to be given reinforcement. Third, the application of the method includes linguistic explanations, asbabul wurud, discussion of fiqh and its ushul, hadith in general, discussion from the sanad side, and differences of opinion of scholars.Penelitian ini membahas tentang ketokohan K.H. Muhajirin Amsar dan telaah metodologis karyanya yaitu kitab Misbah al-Zulam. Penelitian ini menggunakan metode library reseacrh (studi pustaka), dengan menelaah kitab Misbah al-Zulam, diperkuat dengan data sekunder yang bersumber dari buku, artikel, dan berita online yang relevan dengan tema yang diangkat. Penelitian ini menghasilkan kesimpulan bahwa, pertama, K.H. Muhajirin Amsar merupakan ulama kontemporer berpengaruh dari Bekasi yang cukup produktif dalam menghasilkan karya berupa kitab khas pesantren meliputi 34 kitab dari 8 disiplin ilmu agama Islam mencerminkan kedalaman dan keluasan ilmunya. Dari karya-karyanya yang paling populer adalah kitab Misbah al-Zulam yang terdiri dari 8 jilid yang merupakan sharh atau penjelasan lanjutan dari kitab Bulugh al-Maram karya Ibn Hajar al-Asqalani. Kedua, terdapat tiga metode penulisan kitab Misbah al-Zulam yakni tanqil (mengutip), tabyid (pemilahan) dan tahqiq (penguatan). Metode tanqil bebarti menukil dari literatur yang dipakai sebagai referensi, sedangkan metode tabyid berarti melakukan pemilahan naskah yang lebih relevan dengan tema. Adapun metode tahqiq adalah melakukan penguatan dari karya yang telah ditulis secara keseluruhan untuk diberikan penguatan. Ketiga, penerapan dalam metode tersebut meliputi penjelasan kebahasaan, asbab al-wurud, bahasan fiqh dan usul-nya, hadis secara umum, pembahasan dari sisi sanad, dan berbagai perbedaan pendapat ulama.